Interplay between bacterial deubiquitinase and ubiquitin E3 ligase regulates ubiquitin dynamics on Legionella phagosomes - Shuxin Liu; Jiwei Luo; Xiangkai Zhen; Jiazhang Qiu; Songying Ouyang; Zhao-Qing Luo (eLife, 2020)
Legionella pneumophila extensively modulates the host ubiquitin network to create the Legionella-containing vacuole (LCV) for its replication. Many of its virulence factors function as ubiquitin ligases or deubiquitinases (DUBs). Here, we identify Lem27 as a DUB that displays a preference for diubiquitin formed by K6, K11, or K48. Lem27 is associated with the LCV where it regulates Rab10 ubiquitination in concert with SidC and SdcA, two bacterial E3 ubiquitin ligases. Structural analysis of the complex formed by an active fragment of Lem27 and the substrate-based suicide inhibitor ubiquitin-propargylamide (PA) reveals that it harbors a fold resembling those in the OTU1 DUB subfamily with a Cys-His catalytic dyad and that it recognizes ubiquitin via extensive hydrogen bonding at six contact sites. Our results establish Lem27 as a DUB that functions to regulate protein ubiquitination on L. pneumophila phagosomes by counteracting the activity of bacterial ubiquitin E3 ligases.